Bare Metal Stent Use in Type B Aortic Dissection May Offer Positive Remodeling for the Distal Aorta - Sultan, Ibrahim; Dufendach, Keith; Kilic, Arman; Bianco, Valentino; Trivedi, Dhaval; Althouse, Andrew D; Thoma, Floyd; Navid, Forozan; Gleason, Thomas G (The Annals of thoracic surgery, 2018)
Thoracic endovascular aortic repair is increasingly used in acute complicated type B aortic dissection. The objective of this study was to demonstrate evidence of aortic remodeling by using a Proximal ExTension to Induce COmplete ATtachment (PETTICOAT) system in patients with acute complicated type B aortic dissections. From 2013 to 2016, 213 patients with type B aortic dissection were seen at our institution. A total of 33 of those patients underwent thoracic endografting for complicated acute type B aortic dissection. Of these patients, 12 underwent standard thoracic endovascular aortic repair (standard group), and 21 had an additional bare metal stent distal to the covered endograft (PETTICOAT group). Aortic dimensions were measured on the basis of on three-dimensional computed tomographic scans on discharge and at 6 months. There were no differences in baseline characteristics between the standard group and the PETTICOAT group. At 6 months, both the PETTICOAT and standard groups had significant change in aortic diameter, true lumen diameter, and true lumen ratio throughout the thoracoabdominal aorta demonstrating positive remodeling. The change in true lumen ratio was significantly greater at the level of the celiac artery with the PETTICOAT system when compared with the standard group. The use of a PETTICOAT concept with an addition of a bare metal stent distal to the proximal thoracic endograft offers positive aortic remodeling in the thoracoabdominal aorta at 6 months.